THE ALGORITHM OF THE CASE FORMATION DURING THE DEVELOPMENT OF CLINICAL DISCIPLINES IN MEDICAL SCHOOL - Andrey A. Garanin; Reseda M. Garanina (Образование и наука)
The aim of the study is to develop the algorithm of formation of the case on discipline «Clinical Medicine». Methods. The methods involve the effectiveness analysis of the self-diagnosed levels of professional and personal abilities of students in the process of self-study. Results. The article deals with the organization of independent work of students of case-method, which is one of the most important and complex active learning methods. When implementing the method of case analysis in the educational process the main job of the teacher focused on the development of individual cases. While developing the case study of medical character the teacher needs to pay special attention to questions of pathogenesis and pathological anatomy for students’ formation of the fundamental clinical thinking allowing to estimate the patient’s condition as a complete organism, taking into account all its features, to understand the relationships of cause and effect arising at development of a concrete disease, to master new and to improve the available techniques of statement of the differential diagnosis. Scientific novelty and practical significance. The structure of a medical case study to be followed in the development of the case on discipline «Clinical Medicine» is proposed. Unification algorithm formation cases is necessary for the full implementation of the introduction in the educational process in the higher medical school as one of the most effective active ways of learning – method of case analysis, in accordance with the requirements that apply to higher professional education modern reforms and, in particular, the introduction of new Federal State Educational Standards.